The type of motivation that promotes library use and reading at Batasan Hills National High School - Mabuloc, Joanne J.; Obille, Kathleen Lourdes B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
Reading is very important to one's intellectual development and improvement. Through reading, a person could learn so many things in life. Realizing this comes the role of the library as an information provider. The school library should cater to the needs of its users. The librarian, as information expert, plays an important role in promoting the library and reading. This could be done through library displays, bulletins, orientations, and others that help to encourage or influence the students to visit the library and read.
In the public secondary schools, the library usually has one librarian, and they are also, teachers, but some fortunately have two. This is one of the main reasons that they find it hard to manage the library, given a school population of more than a thousand.
Teachers, being educators who meet the students on a regular basis could be a great help in promoting the library and reading. They could influence the students to use the library and read by inspiring and appreciating them. On the other hand, giving school requirements such as assignments, research projects and others may also be effective to students. This study was conducted to determine what type of motivation will make the students use the library and read. The Likert Scale was used in measuring the level of disagreement of students on a five-point scale. The mean and standard deviation were used as the statistical method for this study to determine the effectiveness of each variable of the combination of librarian and teachers together with the positive and negative motivations. To further validate the result, the single factor analysis of variance (ANOVA) was applied.
In general, the study concluded that the librarian's and teachers' positive motivations are effective in making the students use the library and read. Their positive attitudes towards students are effective as well as the teachers' appreciation and inspiration and giving school requirements to the students.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Batasan Hills National High School; High school libraries -- Philippines -- Use studies; High school students -- Philippines -- Quezon City